Black holes, instability and scalar-tensor gravity - Console, Felipe de Carvalho Ceregatti de (2019)
In this work, we review three topics which are relevant on its own but which are also interconnected through the AdS/CFT correspondence: (i) black holes in AdS and its thermodynamics, (ii) nonlinear instability of AdS and (iii) scalar- tensor theory of gravity. Each one of these topics find applications in holography using the above mentioned correspondence. We review the various coordinate systems used to write the AdS metric and discuss the main black holes with AdS asymptotics as well as their thermodynamical properties. We also review current results on linear and nonlinear stability for various spacetimes, presenting a heuristic explanation for the nonlinear instability of AdS. The discussion about alternative theories of gravity is restricted to the case of scalar-tensor theories (Horndeski theories, specially). We study the multipole expansion of the electromagnetic field in the solitonic background of a shift-symmetric scalar-tensor model (up to second order in the scalar field coupling constant with the Gauss-Bonnet term). We find that the multipoles are everywhere regular and finite except for the monopole l = 0, which diverges at the origin of the spacetime coordinates.